Will it blow? : become a volcano detective at Mount St. Helens - Rusch, Elizabeth (Little Bigfoot, 2017)
"This book is an update to a title published in 2007. Mount St. Helens is constantly erupting. It is pushing up a ridge of thick lava that is rebuilding the peak of the mountain that was blown off in 1980. The mountain is being monitored by geologists and volcanologists, all trying to answer the same question: Will it blow? Science is like detective work, and author Elizabeth Rusch presents the work of volcanology in a series of cases that need to be cracked, with Mount St. Helens as the central culprit, a master disguises, adept at sending out false clues. But through an understanding of earthquakes, gases that come from underground, infrared measurement of the earth's temperature, bumps and deformations on the surface of the earth, and kind of rock that is being formed in the crater, readers become volcano detectives. With sidebars about the latest gadgets and gizmos employed at the mountain and activities kids can enact, young people will learn the current science of volcanology and have fun at the same time."--